2019
DOI: 10.1002/mrc.4823
|View full text |Cite
|
Sign up to set email alerts
|

Application of proton field‐cyclingNMRrelaxometry for studying translational diffusion in simple liquids and polymer melts

Abstract: With the availability of commercial field-cycling relaxometers together with progress of home-built instruments nuclear magnetic resonance relaxometry has gained new momentum as a method of investigating the dynamics in viscous liquids and polymer melts. The method provides the frequency dependence of the spin-lattice relaxation rate. In the case of protons, one distin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…48,86 We wish to point out that eld-cycling NMR relaxometry is successfully employed to investigate the dynamics of ILs recently. 26,45,47,63,[87][88][89][90][91][92] Although from a theoretical point of view similar in size, the [C 1 C 1 IM] + cation and the [(CH 3 ) 2 PO 4 ] À anion reveal different reorientation mobilities and diffusivities. The [(CH 3 ) 2 PO 4 ] À anion shows a three to ve times faster reorientation at room temperature compared to the cation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48,86 We wish to point out that eld-cycling NMR relaxometry is successfully employed to investigate the dynamics of ILs recently. 26,45,47,63,[87][88][89][90][91][92] Although from a theoretical point of view similar in size, the [C 1 C 1 IM] + cation and the [(CH 3 ) 2 PO 4 ] À anion reveal different reorientation mobilities and diffusivities. The [(CH 3 ) 2 PO 4 ] À anion shows a three to ve times faster reorientation at room temperature compared to the cation.…”
Section: Resultsmentioning
confidence: 99%
“…For such systems the molecular motion and relaxation properties can be described more efficiently by a distribution of correlation times rather than a single correlation time and an order parameter. [44][45][46][47][48] Therefore, the empirical Cole-Davidson (CD) approach 49,50 (eqn (9)) is widely used in literature for quantitative analysis of relaxation data with distributed correlation times. In eqn (9) the parameter b (0 < b # 1) describes the width of the distribution and s CD is related to s c by s c ¼ bs CD .…”
Section: T Totalmentioning
confidence: 99%
“…Conventionally, the spin–lattice relaxation rate R 1 (ω) is measured as a function of temperature for a few frequencies only, and a model-independent extraction of the underlying spectral density (or of the susceptibility) is elusive. With the advent of the field-cycling (FC) technique employing commercial , or home-built , relaxometers, the situation improved. Proton FC NMR ,,,, measures the frequency-dependent rate R 1 (ω) typically in a range from 10 kHz to 30 MHz, in home-built machines even from 100 Hz to 40 MHz .…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of the field-cycling (FC) technique employing commercial , or home-built , relaxometers, the situation improved. Proton FC NMR ,,,, measures the frequency-dependent rate R 1 (ω) typically in a range from 10 kHz to 30 MHz, in home-built machines even from 100 Hz to 40 MHz . Yet, the about 3 frequency decades covered by commercial instruments are still too narrow to access the broad relaxation spectra in viscous liquids.…”
Section: Introductionmentioning
confidence: 99%
“…The main components of fats, triacylglycerols (TAGs), can be considered to be branched polymers, so it is plausible to hypothesise that their dynamics cover orders of magnitude in time, and thus frequencies, similarly to other polymers, and even phospholipids . Moreover, Eads et al reported that structural differences in TAGs are observable at frequencies between tens to hundreds of kilohertz.…”
Section: Introductionmentioning
confidence: 99%